The Correlation between Students’ Vocabulary Mastery and Speaking Skill - Suryanto, Bradhiansyah Tri; Imron, Ahmad Arif; Prasetyo, Diyah Ayu Rike (Universitas Nurul Jadid, 2021)
In an increasingly advanced globalization era where the ability to speak English is a must in keeping up with the times. An analysis of the correlation between vocabulary mastery and students' speaking skills in English is needed. This is because vocabulary mastery is the main point for students to have good speaking skills. This study aims to determine the relationship between vocabulary mastery and speaking skills. This research uses a quantitative approach with a correlation study type. The sample in this study was 52 respondents in the second semester of the Department of English Education, the University of Nurul Jadid using the purposive sampling technique. Data analysis using the Pearson Product Moment formula to determine whether there are a correlation and the level of correlation between mastery of English vocabulary and speaking skill.